Effect of Deposition Temperature on the Surface Morphology of the Radio Frequency Plasma Enhanced Chemical Vapour Deposition Grown Diamond Like Carbon Films - Maheswaran1, R.; John Thiruvadigal1, D.; Gopalakrishnan2, C.; Ramaswamy2, Shivaraman (Asian Journal of Chemistry, 2013)
The diamond like carbon (DLC) films have been grown by radio frequency plasma enhanced chemical vapour deposition (RF-PECVD) in methane-argon plasma. In plasma enhanced chemical vapour deposition, the plasma sheath potential drop arising due to argon plasma was utilized to grow the diamond like carbon film on silicon (100) substrates without using any external negative bias voltage. The morphological variations during the growth of the diamond like carbon film as function of deposition temperature have been studied. A set of experiments were carried out by varying the deposition temperatures (room temperature, 100, 200 and 400 ºC) and by keeping other parameters constant.